2020
DOI: 10.1002/pa.2417
|View full text |Cite
|
Sign up to set email alerts
|

Usage of social media during the pandemic: Seeking support and awareness about COVID-19 through social media platforms

Abstract: Social media have become popularly use to seek for medical information and have fascinated the general public to collect information regarding corona virus pandemics in various perspectives. During these days, people are forced to stay at home and the social media have connected and supported awareness and pandemic updates. The present study aims at highlighting the present situation of Indonesian society, where the outbreak position is quite high. The study collects the data from social media users from March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 37 publications
2
70
0
8
Order By: Relevance
“…Previous research has suggested that misinformation from media usage, particularly social media usage through Facebook or Twitter, can be more harmful to one's mental health (Allington et al 2020;Limaye et al 2020;Ni et al 2020). Whilst other evidence suggest social media may be beneficial in creating social support during this pandemic; however, this is only applicable for those who have access to these resources (Carlsen et al 2020;Saud et al 2020). Based off World Health Organization (2020) guidelines, while socialising over media platforms such as Facetime and Whatsapp can be useful for social support, it is important not to spend a significant portion of the day checking and scanning media platforms for information.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that misinformation from media usage, particularly social media usage through Facebook or Twitter, can be more harmful to one's mental health (Allington et al 2020;Limaye et al 2020;Ni et al 2020). Whilst other evidence suggest social media may be beneficial in creating social support during this pandemic; however, this is only applicable for those who have access to these resources (Carlsen et al 2020;Saud et al 2020). Based off World Health Organization (2020) guidelines, while socialising over media platforms such as Facetime and Whatsapp can be useful for social support, it is important not to spend a significant portion of the day checking and scanning media platforms for information.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, those described in Table 2 and Table 3 , reflect major cancer-related services that were covered by the CPGs up until mid-November 2020. In addition, social media platforms used by patient advocacy groups, such as Facebook, Instagram, and Twitter, were not explored but such outlets may have provided pertinent resources to cancer communities during the COVID-19 pandemic [ 48 ]. However, we assumed that any information delivered to the public through social networks would have been communicated by the cancer organizations on their websites.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al and Saud et al have especially highlighted the importance of social media as a viable tool for rapid knowledge dissemination during the early phase of COVID-19. 15 , 16 To combat the misinformation, the Saudi Ministry of Health (MOH) has started broadcasting awareness videos through social media platforms like Facebook, Twitter, and Instagram. Additionally, the MOH has also initiated awareness programs to educate the public on not just the virus, but also proper ways of washing hands and wearing masks, the importance of curfew, and how the aforementioned measures and social distancing can help control the rate of viral transmission.…”
Section: Introductionmentioning
confidence: 99%